```Question 280963
It says there are 6 steps involved in the proper formatting of these questions involving
a) moving the constant term to the right side of the equation,
b) multiplying each term by 4 times the coefficient of the x squared term,
c) squaring the coefficient of the original x term,
d) taking the square root of both sides,
e) and then setting the left side of the equation equal to the positive square root of the number on the right side and
f) then setting the left side of the equation equal to the negative square root of the number on the right side.
--------------------------
Let's try one:
(1) x^2-2x-13=0
a) x^2 - 2x = 13
b)4x^2 - 8x = 52
c)"square the coefficient of the original x term" gives you 4
d)sqrt(4x^2-8x) = sqrt(52)
e)sqrt(4x^2+8x) = sqrt(52)
f)sqrt(4x^2+8x) = -sqrt(52)
============================
As far as I can see those steps get you nowhere.
Step "c" is particularly puzzling because you don't do anything
with the squared coefficient.
Good luck with the rest.
Cheers,
Stan H.
============================

(2) 4xsquared-4x+3=0
(3) xsquared+12x-64=0
(4) 2xsquared-3x-5=0
```